2022
DOI: 10.3390/ani12192625
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phytobiotic Composition on Production Parameters, Oxidative Stress Markers and Myokine Levels in Blood and Pectoral Muscle of Broiler Chickens

Abstract: The aim of this study was to evaluate the effect of dietary level of a phytobiotic composition (PBC) on production parameters, oxidative stress markers and cytokine levels in the blood and breast muscle of broiler chickens. The experiment was performed on 48 one-day-old female Ross 308 broiler chickens divided into three groups (n = 16) fed the control diet (without PBC), and a diet supplemented with 60 or 100 mg/kg of PBC. After 35 days of feeding, blood and breast muscle samples were collected for analyses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Pectoral muscle (PM) growth is considered an important factor in evaluating the feeding regime and overall chicken growth [ 77 , 78 ]. The reason is that PM has the lowest fat deposits compared to other parts [ 61 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pectoral muscle (PM) growth is considered an important factor in evaluating the feeding regime and overall chicken growth [ 77 , 78 ]. The reason is that PM has the lowest fat deposits compared to other parts [ 61 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study of phytobiotics shows ambiguous indicators of poultry productivity, so some authors make the claim that phytobiotics do not show a significant effect [ 42 , 43 ]. Others, on the contrary, characterize more intensive growth [ 8 , 9 , 14 , 22 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results complement previous analyses and provide new, promising data on the possibility of reducing and controlling bacteria in broiler flocks responsible for foodborne disease in humans. Previous studies conducted on an in vivo model on broiler chickens have shown that phytobiotic mixtures can be effective alternatives to antibiotic growth promoters, improving selected production parameters, but also affecting myokines and interleukins related to immunity and muscle growth [ 45 ]. The two mixtures tested in the presented study, after confirming their effectiveness on an in vitro model, could be a perfect complement to a comprehensive antibiotic reduction program in poultry production with the use of various alternatives to classic antibiotics, including other phytobiotic mixtures.…”
Section: Discussionmentioning
confidence: 99%